Combatting Bullying in School and Its Consequences - Kaltsas , Evangelos Panagiotis; Kaltsas , John (Research Highlights in Language, Literature and Education Vol. 6, 2023)
The study focuses on what school violence is, its characteristics, its forms, its effects and ways it can be prevented. School violence and bullying have a considerable number of consequences for both the victim and the aggressor, as they will both face many difficulties, both in their smooth psychosomatic development, and their subsequent adult life. The study’s material consists of articles related to the topic, found in Greek and International \(και\) databases, the Google Scholar, and the Hellenic Academic Libraries (HEAL-Link)The study of the phenomenon of school violence is important since it constitutes the base on top of which prevention schedules can be designed. Violence prevention measures regarding the school facilities themselves can also be taken. Parents must always act civilly and without violence inside their homes, and teachers can support the development of positive relationships between the children. The abuse and isolation of the children can be reduced in this way. Schools must provide the children with safety. The students that are the most likely to become bullying victims especially should be under the impression that they are being protected in the school.